Development of e-module based on problem-based learning on human respiratory organs for grade V UPT SDN 11 Tiumang, Dharmasraya District - Elsa Rahmawati; Zaka Hadikusuma Ramadhan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop an E-Module based on problem-based learning using material related to the Human Respiratory System. This study uses quantitative and qualitative methods. This study is a development research project (Research and Development) utilising the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). To test the validity of the E-Module product based on problem-based learning (PBL) development, it requires two media experts, two language experts, and two design experts. The results of the study indicate that the validation process of the e-module based on Problem-Based Learning, using material on human respiration, to improve students' creative thinking skills yielded "very decent" results. Therefore, it can be said that this product is very suitable for use as a teaching material in learning about the human respiratory system in science. This problem-based learning E-module also received a very positive response from all research subjects, as evidenced by both teacher and student assessments. It can be concluded that the researcher has developed an E-Module that aligns with the research objectives.